Application of Evolutionary Algorithms to Predict Mechanical Properties on Natural Fibers – A Review. Issue 1 (October 2020) - Prasanth Kumar, R; Rajmohan, T; Vijayan, D
Abstract: Natural fibers are an abundant source in nature, having an inherent property in which include biodegradable, decomposable and cost efficient. Moreover, they exhibit extensive mechanical properties such as tensile modulus, flexural modulus than synthetic fibers when reinforcing polymer resins. However, adding inappropriate levels of quantity of resins misleads on obtaining desired mechanical properties. Several approaches have been utilized in the past decades to get desired mechanical properties on the natural fibers, in which applying evolutionary algorithms are the most recent and familiar in the composite research community. Therefore, in this study an application of evolutionary algorithms on natural fibers are presented. This objective of the review is to provide detailed information of the natural fibers along with its recent algorithmic approaches. Moreover, the effect of various treatments and its changes in mechanical, thermal and electrical properties of matrix.